Homonym - Fernandez, Liam (Auckland University of Technology, 2018)
“It’s too bad she won’t live. But then again, who does?” – Gaff (Blade Runner, 1982) While this line in Ridley Scott’s 1982 cult-classic film speaks of the threat that will come for the replicant Rachel, it is also suggestive regarding the nature of humanity, love, and precocity of life. My accompanying creative thesis; a novel titled Homonym, draws inspiration from these notions and seeks to, not so much definitively answer the many questions these philosophical ideas may pose, but discuss and probe them through the mode of creative fiction writing. By applying a number of codes from the science fiction genre, and more specifically the cyberpunk sub-genre, Homonym attempts to flesh out ideas around human nature which serve as motivation for the work. In order to provide coherence to the areas discussed throughout this exegesis, it is perhaps first important to provide an outline of the story.
Keywords: Cyberpunk; Fiction; Post-apocalyptic; Science-fiction